Pelatihan Pemanfaatan Limbah Pertanian Untuk Meningkatkan Kesadaran Masyarakat Dalam Pengolahan Limbah Pertanian Menjadi Biomassa Di Desa Batu Mekar Kecamatan Lingsar - Muhammad Rivaldi Harjian; Ida Ayu Sri Adnyani; Supriyatna; abdul Natsir; I Ketut Perdana; Akbar Tawaqqal (Universitas Mataram, 2026)
Agricultural waste such as rice straw and wood waste has great potential to be utilized as an environmentally friendly biomass energy source. However, the community in Batu Rimba Hamlet, Batu Mekar Village, Lingsar District, still tends to openly burn this waste, causing environmental pollution and not providing optimal economic value. This community service activity aims to increase community understanding, awareness, and interest in processing agricultural waste into biomass fuel. The implementation method is carried out through the stages of problem identification, socialization, training, direct practice of biomass production, and activity evaluation using a questionnaire for 20 training participants. The materials provided include biomass potential, the impact of open burning, and techniques for processing wood waste and straw into alternative fuels such as biomass briquettes. The results of the activity showed that the training program successfully increased community capacity with an average level of understanding of 83.25%, awareness of 84.50%, and interest and readiness of 84.75%. Overall, the average evaluation score reached 84.17%, which is included in the high category. In addition to improving community knowledge and skills, this activity also fosters awareness of the importance of sustainable agricultural waste management and has the potential to open up renewable energy-based business opportunities at the local level. Therefore, training on utilizing wood and straw waste as biomass can be an educational and practical solution to support more valuable and environmentally friendly agricultural waste management. Keywords: agricultural waste, biomass, briquettes, community training, renewable energy.